An experimental limit on the intrinsic charm component of the nucleon - Aubert, J; Bassompierre, G; Becks, K; Best, C; Böhm, E; de Bouard, X; Brasse, F; Broll, C; Brown, S; Carr, J; Clifft, R; Cobb, J; et al. (1982)
Charm production has been studied through multimuon events produced in 250 GeV μ+-interactions. The measured dimuon cross section is in agreement with the photon gluon fusion model at low values of Bjorken x within statistical and systematic errors. At larger values of xBi the data do not support the magnitude of intrinsic charm used to explain hadro-production of charm. Upper limits on the intrinsic charm content of the nucleon are derived from the data. © 1982.